1996
DOI: 10.1042/bj3141001
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship of cytoplasmic 5′-nucleotidase substrate sites

Abstract: Various 5'-nucleotidases (EC 3.1.3.5) exist in vertebrate tissues. The sequence and cDNA cloning of the membrane-bound ecto-5'-nucleotidase (e-N) and one of the cytosolic isoenzymes, IMP-preferring (c-N-II), but not the cytosolic AMP-preferring form (c-N-I), have been reported. While c-N-II has a broad tissue distribution, c-N-I is found only in vertebrate heart. The published data on substrate specificity involve mainly the naturally occurring nucleoside monophosphates, without a systematic structure-activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…5A), followed by a rise in MPrib. This suggests that the MPrib is made by dephosphorylation of tIMP by a phosphatase or nucleotidase (Skladanowski et al, 1996;Hunsucker et al, 2001), followed by rapid excretion of the nucleoside via a nucleoside transporter (Baldwin et al, 1999). As expected, intracellular tXMP and TXrib concentrations follow the rise in tIMP in the cells with some delay (Fig.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…5A), followed by a rise in MPrib. This suggests that the MPrib is made by dephosphorylation of tIMP by a phosphatase or nucleotidase (Skladanowski et al, 1996;Hunsucker et al, 2001), followed by rapid excretion of the nucleoside via a nucleoside transporter (Baldwin et al, 1999). As expected, intracellular tXMP and TXrib concentrations follow the rise in tIMP in the cells with some delay (Fig.…”
mentioning
confidence: 81%
“…Any mechanism that reduces the intracellular concentration of tGMP may act as a potential resistance mechanism. As mentioned above, 5Ј-nucleotidase reduces the tNMP pool and has been linked to thiopurine resistance (Rosman et al, 1974;Skladanowski et al, 1996). Furthermore, TPMT methylates 6MP, forming MeMP, which reduces the 6MP concentration and toxicity (Lennard et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The substrate specificity of 5´NTs is based on its recognition of the nucleobase. Not surprisingly, hydrogen-bond formation with the substituent in the 6-position of the purine ring and the hydrophobic attractions play major roles in the substrate specificity of 5´NTs [164]. The electron pair on N-1 is important in substrate binding of cN-II but is not a prerequisite for cN-I.…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…Likewise, human 5 0 -nucleotidase activity was affected by ADP in range concentrations from 0 to 2 mM, increasing its specific activity from 1 to 38 mM Pi/min/mg protein (Hunsucker et al, 2001). On the other hand, when Skladanowski et al (1996) were working with 5 0 -nucleotidase from rat they observed an ADP activator effect in range from 0 to 1 mM, in which its specific activity increased from 0.1 to 0.3 U/ mg. Nevertheless, both ATP and ADP may also act as inhibitors depending on the enzyme source (Naito & Lowenstein, 1981).…”
Section: Effect Of Atp and Adpmentioning
confidence: 99%
“…Skladanowski, Hoffmann, Krass, Jastorff, and Makarewicz (1996) detected a biphasic behavior in purified enzyme of pigeon heart, 5 0 -nucleotidase was activated in the range from 0 to 500 mM with a max peak of 50 mM. Willadsen, Nielsen, and Riding (1989) reported 70% Figure 3.…”
Section: Effect Of Nacl Mgcl 2 and Caclmentioning
confidence: 99%